NOTES ON THE MEXICAN SILVER MINING INDUSTRY IN THE/ 1590´s. - Bakewell, J.P. (HUMANITAS DIGITAL, 2021)
THAT SILVER MINING was an important part of the economy of Mexico during the whole colonial period needs no stressing. The quest for mines and the subsequent exploitation of ores were responsible for the early exploration of many areas, for much of the growth of internal trade, and for agricultural development in many regions. Silver itself was the vital fluid of the body economic, the major export of the colony, and one of the major incentives impelling Spain to maintain her exclusive control over many great and empty tracts of territory. Despite these and other familiar qualities of the industry, the ubiquity of mining in Mexico still surprises. The few great names ring out in both manuscripts and ancient and modern historical wri tings: Taxco, Pachuca, Guanajuato, San Luis Potosi, Zacatecas, Parral. These were indeed the places from which most silver came. But the dozens of lesser centres which existed, and which played their part in their day, are long gone from view.